THE ROLE OF TELEVISION ADVERTISEMENTS TOWARD HOUSEWIVES BUYING PATTERN IN MANADO CITY - Delimayanti, Anisa (FEB Universitas Sam Ratulangi Manado, 2014)
Advertisement used as a major tool in marketing managers which helps enable the companies to sell goods and services. Television advertisement is the main media in current time. This research is designed to have a clearer image and deeper understanding about the role of television advertisements among housewives buying pattern in Manado city. The method used qualitative research methodology with case study approach which provide descriptive insight about housewives’ buying pattern toward television advertisement in Manado. Sample of this research are 11 housewives that watch television advertisements and influence their buying pattern in Manado. The findings, Television as media information are better than other media among the housewives in Manado. Advertisements preferred by housewives are, it presented the product advances, price sales, branded, and security before they conduct a long term use. Recommendation from social and environment help housewives to make personal decision making on purchasing. This research suggests the companies to present advertisement more informative points such as product advances, quality, price promo, prizes, demonstrations and testimonies in their advertisements on television. Companies need to locate the advertisement on certain estimated time of the viewers watch events in order to reduce broadcast frequency expenses. Keywords: television advertisement, buying pattern